HUBUNGAN TINGKAT PENGETAHUAN MENOPAUSE DENGAN TINGKAT KECEMASAN PADA WANITA MENOPAUSE DI DESA NGABEYAN KECAMATAN KARTASURA KABUPATEN SUKOHARJO - Ningsih, Endang Dwi; Setyaningsih, Rahayu (Jurnal AKPER GSH, 2016)
Introduction: Menopause is the last menstrual period experienced, usually will have a tough time include: difficulty sleeping, night sweats, emotions are difficult to control and so on, which increase to the effects of anxiety. With regard to the foregoing, the authors are interested in studying the "Relationship with Knowledge about Menopause with Level of  Anxiety Menopause’s Women in Ngabeyan Kartasura District of Sukoharjo".Purpose of the study: to determine the relationship of the level of knowledge about menopause with  level of anxiety menopause’s women in  Ngabeyan Kartasura District of Sukoharjo district.Desigan and Subjects: this research is corellation with cross sectional  design.  The study population was female menopause in   Ngabeyan Kartasura District of Sukoharjo regency as many as 40 people. Samples in this study were 36 postmenopausal women in Ngabeyan Kartasura District of Sukoharjo based Krecjie table. The sampling technique used in this research is accidental sampling technique.Results: From the results of Chi-Square test with α = 0.05 (5%) gained by 0.02 so that the value of p <0.05, which means that Ho refused and Ha accepted.Conclusion There is a relationship between the level  knowledge of menopause with anxiety levels in postmenopausal women at  Ngabeyan Kartasura District of Sukoharjo.Keywords: knowledge about menopause, anxiety